Extrication of biodiesel feedstock from early stage of food waste liquefaction / Maridah Binti Mohd Amin - Mohd Amin, Maridah (2015)

(untitled)
This study aims to provide alternative solution in the management of domestic waste and the possibility of using the extracted free fatty acid (FFA) in the food waste as the feedstock for the production of biodiesel. The main concern of acquiring the FFA from the food waste is the challenge which lies during its extraction due to high water content. Prior to the pre-treatment of food waste via the natural biological cycle, the selection of best FFA extraction method was performed on the fresh food waste. It was found that the use of Reflux method is more effective compared to the Soxhlet method. Both extraction methods used two solvents, dichloromethane and n-hexane. Despite of using the different solvent, similar profile FFA and amount have been observed during both extractions. The effectiveness of choosing Reflux method is because it does not require the drying process, when compared to Soxhlet. The following experimentation was carried out to extract the FFA on the hydrolysed food waste during its liquefaction process. This experiment used two types of hydrolysed food waste, natural liquefaction and enhanced liquefaction process, with and without introduction of seed sludge, respectively. Both liquefaction processes had undergone beyond the hydrolysis stage, which has included the acidification stage. Results have shown that the natural liquefaction of food waste had provided higher yield of FFA, specifically in 72 hours liquefaction stage. In a different experiment, major FFA profiles which were obtained during the natural 72 hours of liquefaction process was transesterification and found to produced highly unsaturated fatty acid methyl ester (FAME) ranging from C16 to C18. Nevertheless when the transesterification of such FFA using C2-C5 modelled compound, the process had produced the opposite profiling of FAME, which mainly saturated. Therefore, natural liquefaction of food waste has the potential to produce the feedstock for biodiesel. Keywords: food waste, free fatty acid, extrication, biodiesel, esterification